Information retrieval agent for E-PAFA / Muzazila Mustari - Mustari, Muzazila (2005)
PAFA in Malay translation is Perkara Asas Fardhu Ain. The basic knowledge offardhu ain to teach the Islamic knows and slave to Allah. The objective of this project is to develop E-PAFA prototype focus on the basic information of salat and fast. The prototype that covers the basic knowledge of fardhu ain and the target user are muallaf and children ages between 10 to 17 years old. The project methodology involved are project review, data and knowledge acquisition, system design, system implementation, and system testing and Debugging. Using this prototype, the Islamic can get the solution of the problem easier. The user can retrieve and gain their knowledge effectively.